The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/app10010129
|View full text |Cite
|
Sign up to set email alerts
|

Model Evaluation for Forecasting Traffic Accident Severity in Rainy Seasons Using Machine Learning Algorithms: Seoul City Study

Abstract: There have been numerous studies on traffic accidents and their severity, particularly in relation to weather conditions and road geometry. In these studies, traditional statistical methods have been employed, such as linear regression, logistic regression, and negative binomial regression modeling, which are the most common linear and non-linear regression analysis methods. In this research, machine learning architecture was applied to this problem using the random forest, artificial neural network, and decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 48 publications
0
18
0
1
Order By: Relevance
“…The activation function is responsible for making a neural network non-linear [19]. The tangent, hyperbolic, sigmoid, and linear functions are commonly chosen activation functions [20].…”
Section: Methodsmentioning
confidence: 99%
“…The activation function is responsible for making a neural network non-linear [19]. The tangent, hyperbolic, sigmoid, and linear functions are commonly chosen activation functions [20].…”
Section: Methodsmentioning
confidence: 99%
“…The results of the study revealed that AdaBoost outperformed the other methods. Furthermore, in [25][26][27], the authors investigated road accidents using real-life data considering methods such as J48, LSSVM, and RF. Other studies used probabilistic reasoning models such as Bayesian networks, or BNs, [28][29][30][31][32], with [28] performing a comparison between BNs and regression models.…”
Section: Related Studiesmentioning
confidence: 99%
“…Farhangi et al [10] Accident-risk modeling and mapping Lee et al [25] Accident severity prediction Mestri et al [26] Identification of accident-prone locations Al-dogom et al [21] Spatio-temporal analysis for accidents prediction Fan et al [27] Identification of accident black spots and analyzing their characteristics…”
Section: Paper Machine Learning Applicationmentioning
confidence: 99%